23.2k views
6 votes
If possible step by step explanation. thank you!

If possible step by step explanation. thank you!-example-1

1 Answer

9 votes

Answer:

A

Explanation:


((3x^(2) )^(1)/(2) )/(3^(1)/(2) ) =3


(3x^2)^(1)/(2) = 3^(1)/(2) x

Remember that
(x^b)/(x^c) =x^(b-c)

Using that
(3^(1)/(2)x )/(3^(1)/(2) )=3^(1/2x-1/2)=3^((x-1)/2)


3^(x-1)/(2) =3^1

So we can say:
(x-1)/(2) =1, because the bases are the same

We can multiply both sides of the equation by 2. We get x-1=2, and x=3. Which is A.

User Barclay
by
5.3k points